2016
DOI: 10.1007/s10877-016-9931-8
|View full text |Cite
|
Sign up to set email alerts
|

Transcutaneous near-infrared spectroscopy for monitoring spinal cord ischemia: an experimental study in swine

Abstract: We aimed to assess the ability of near-infrared spectroscopy (NIRS) to detect spinal cord ischemia, and to evaluate changes in regional oxygen saturation (rSO) following recovery of spinal cord circulation and cerebrospinal fluid drainage. Four 12-month-old female swine weighing 28.7-29.5 kg were acquired for this study. NIRS probes were placed along the midline of the upper (T6/7) and lower (T9/T10) thoracic vertebrae. The thoracic aorta was clamped distal of the left subclavian artery to induce spinal ischem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 20 publications
0
6
0
Order By: Relevance
“…Previous experimental and clinical studies on cnNIRS have shown that although in heterogeneous setups and study protocols, it reflects oxygenation changes after aortic crossclamping and distal aortic perfusion in real-time. 7,8,[11][12][13]20 On the basis of these and other studies, cnNIRS emerged as a promising new and economic method, potentially guiding extensive aortic procedures by giving real-time feedback on spinal cord perfusion. 21…”
Section: Previous Experience With Collateral Network Near-infrared Spectroscopymentioning
confidence: 98%
See 1 more Smart Citation
“…Previous experimental and clinical studies on cnNIRS have shown that although in heterogeneous setups and study protocols, it reflects oxygenation changes after aortic crossclamping and distal aortic perfusion in real-time. 7,8,[11][12][13]20 On the basis of these and other studies, cnNIRS emerged as a promising new and economic method, potentially guiding extensive aortic procedures by giving real-time feedback on spinal cord perfusion. 21…”
Section: Previous Experience With Collateral Network Near-infrared Spectroscopymentioning
confidence: 98%
“…Whether in addition to lumbar cnNIRS optodes, mid and especially lower thoracic cnNIRS measurements also are necessary for a complete and consistent oxygenation mapping of the CN is yet unclear and is the focus of ongoing research. The limitation of optode placement directly above the vertebrae has been acknowledged by their respective authors, who suggested that measuring surrounding tissue may enable indirect cord monitoring via the paraspinal CN, 7,20,23 a concept that represents the rationale for current cnNIRS monitoring practice. 11,12,23 Although sensitivity of cnNIRS after stent deployment during endovascular aortic repair was recently published in 2 reports (total of 3 patients), 21,22 available data from previous case series and ongoing clinical investigations suggest that lumbar cnNIRS does not reliably pick up relevant changes in oxygenation during endovascular procedures in humans (not experiencing procedure-related SCI).…”
Section: Sensitivity Of Collateral Network Near-infrared Spectroscopy To Segmental Artery Occlusionmentioning
confidence: 99%
“…NIRS estimates mixed tissue hemoglobin oxygen saturation levels of the arterial, venous, and capillary blood within the field of view [10,11], which allows the oxygen supply-and-demand balance to be evaluated under differing conditions. Similar to what has been done with the cerebrum, several studies have measured spinal cord oxygenation using NIRS directly [12][13][14][15] (via surgical procedure or thin fiber-optic probe placed in the intrathecal or epidural space) or indirectly [16][17][18][19] (via paraspinal muscle oxygenation monitoring, based on the paraspinal collateral network concept) to monitor spinal cord perfusion, but few studies to date have assessed spinal cord autoregulation using this method.…”
Section: Introductionmentioning
confidence: 99%
“…30 After publication of that review, a fourth-generation software was released and tested, concluding that the accuracy of CO values measured with this version has improved greatly compared with previous versions but still did not reach a clinically sufficient level (ie, a percentage error <30%). [31][32][33] Another uncalibrated PCA system for monitoring CO is the ProAQT/PulsioFlex system (Pulsion-Getinge, Feldkirchen, Germany). It essentially uses the PCA-based algorithm of the PiCCO system (Pulsion-Getinge), however, without the possibility of external validation by TPTD.…”
Section: Transition To Minimally Invasive and Noninvasive Hemodynamicmentioning
confidence: 99%